2019
DOI: 10.1071/hc18103
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist integration into general practice in New Zealand

Abstract: IntroductionPharmacist integration into general practice is gaining momentum internationally, with benefits noted in reducing medication errors, improving chronic disease management and alleviating general practitioner workforce shortages. Little is known about how general practice pharmacists are working in New Zealand. AimThis study characterised the current landscape of pharmacist integration into general practice in New Zealand. MethodsAn online questionnaire was developed, piloted and distributed to all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…On the contrary, supportive practice and the presence of an experienced pharmacist in the workplace were identified as facilitators to integration into GP. Besides England [17], similar findings have also been reported by other studies involving different international healthcare systems including Canada [37,39], Australia [14] and New Zealand [40]. A number of policies has been introduced recently in the UK and not just in England to expand the current involvement of clinical pharmacists in general practice [18,34,41].…”
Section: Discussionsupporting
confidence: 80%
“…On the contrary, supportive practice and the presence of an experienced pharmacist in the workplace were identified as facilitators to integration into GP. Besides England [17], similar findings have also been reported by other studies involving different international healthcare systems including Canada [37,39], Australia [14] and New Zealand [40]. A number of policies has been introduced recently in the UK and not just in England to expand the current involvement of clinical pharmacists in general practice [18,34,41].…”
Section: Discussionsupporting
confidence: 80%
“…With the expansion of pharmacists’ roles, pharmacists have been included in primary healthcare teams to provide collaborative patient care in many countries. The co-location of pharmacists within primary healthcare teams has been studied in the United States of America (USA), United Kingdom (UK), Canada, Australia, The Netherlands, Ireland, Brazil, New Zealand, and Malaysia [ 1 8 ]. Studies from the USA, UK, and Canada have reported that the inclusion of pharmacists into primary healthcare teams has improved patients’ health outcomes and benefited patients in other ways [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two surveys identified that the Southern DHB is among several regions that have progressed the furthest with implementation. 25,26 The WellSouth Primary Health Network is the primary health organisation…”
Section: Introductionmentioning
confidence: 99%